Compressive strength assessment of sulfate-attacked concrete by using sulfate ions distributions. (26th July 2021) - Cheng, Hanbin; Liu, Tiejun; Zou, Dujian; Zhou, Ao
Highlights: The performance of concrete under sulfate attack and dry-wet cycles is investigated. A newly defined index is proposed to describe the progress of sulfate attack. A novel method is proposed to assess the performance of sulfate-attacked concrete. Abstract: Sulfate attack is a major cause of concrete durability deteriorations. Mass loss, strength reductions, and expansive strain of concrete specimens are generally used in laboratory testing to identify the resistance of concrete materials to sulfate attack. However, these indicators cannot be directly used to quantitatively predict the bearing capacity of actual concrete structures under sulfate attack. There exists a significant size effect between laboratory and engineering size concrete components. In this study, the durability performance of concrete specimens, exposed to sulfate attack and dry–wet cycles, was investigated. Mass loss, dynamic elastic modulus, compressive strength, and sulfate ions distributions of deteriorated concrete were measured over time. Test results indicate that the newly defined integral area of sulfate ions distributions is a suitable index to describe the non-uniform deteriorations behavior of sulfate–attacked concrete; and a novel method based on the homogenizations theory is proposed to predict the deteriorations level of components of attacked concrete structures, which provides a potential use in assessing the loading capacity of actual concrete structures based on accelerated test results in a laboratory.